Cost Implication of a Community-Based Pediatric Palliative Care Program - Ying (Elaine) Wang; Wenyun Yang; Megan Young; Kerri Padgett; Elaine Gabovitch; Ning Zhang; Jianying Zhang; Scot T. Bateman (Journal of Palliative Medicine, 2026)
Background: Massachusetts’ Pediatric Palliative Care Network (PPCN) program provides community-based pediatric palliative care (CBPPC) to children with life-limiting conditions and their families. PPCN offers comprehensive clinical services, integrative therapies, and case management. Objectives: This study explores whether PPCN can maintain or reduce health care utilization and costs. Design: PPCN children were compared with a propensity score matched group. Bivariate and regression analyses were conducted to compare outcomes between these two groups based on program data, Medicaid claims data, and vital records from 2015 to 2021. Setting/Subjects: A sample of 126 deceased PPCN and non-PPCN children, respectively. Measurements: Chief outcomes included service use (inpatient/outpatient service, hospice, telehealth, length of stay), place of death, clinical symptoms, psycho-social well-being proxies, and health care cost. Results: Compared to 126 non-PPCN children, PPCN children had similar inpatient hospital admissions, emergency department visits, outpatient visits, hospice use, and telehealth use, but the length of stay was shorter. PPCN children were less likely to have intensive care unit admissions Adjusted Odds Ratio (aOR = 0.19, 95% Confidence Interval (CI): [0.06, 0.65]) with similar clinical symptoms and less ventilator use (aOR = 0.79, 95% CI: [0.78, 0.80]). A 20.6-point higher percent of PPCN children died at home ( p < 0.001). PPCN children with neoplasm ( n = 37), both neoplasm and genetic disease conditions ( n = 11), or who died at home ( n = 50) incurred at least 10% less cost, inclusive of program cost, than non-PPCN children ( n = 37, 11, and 24). Conclusions: CBPPC maintains or reduces health care utilization and costs for children at the end of life. It potentially saves costs for those with the most complex medical conditions or having died at home, which indicates the potential cost-effectiveness of PPCN because of its proven effect to improve quality of life for program children and their caregivers.